A new species of the spider genus Phlogiellus (Araneae, Theraphosidae) from Hainan, China - Lin, Yejie; Li, Shuqiang; Chen, Haifeng (Zootaxa, 2021)
The genus Phlogiellus Pocock, 1897 of the spider family Theraphosidae Thorell, 1869 includes 25 species from Southeast Asia, of which three have been recorded in China (Li 2020): P. bogadeki Nunn, West & von Wirth, 2016 and P. xinping (Zhu & Zhang, 2008) from Hong Kong and P. watasei (Kishida, 1920) from Taiwan. Here, we describe a new Phlogiellus species from Hainan, China: P. quanyui sp. nov.